Observation of Novel Multifunctionalities in Monolayer CdO. Issue 12 (6th September 2018) - Ekuma, Chinedu E.
Abstract: Multiferroicity, especially ferroelectric, usually fades away at the atomic limit of materials. Here, based on multiscale ab initio many‐body calculations employing first‐principles density functional theory, density functional perturbation theory, the self‐consistent quasiparticle Green function and screened Coulomb method, and the Bethe–Salpeter equation, intrinsic spontaneous polarization and ferroelectricity in monolayer CdO are observed. Using the data, a rather high electromechanical coupling coefficient of ≈6.26% is predicted. The results further reveal a direct optical bandgap of ≈3.16 eV. This direct excitation is dominated by strongly bound excitons with a binding energy of ≈1.09 eV. The predicted multifunctionalities of monolayer CdO are crucial for emerging applications in optoelectromechanical nanodevices and provide insights into its novel properties. Abstract : Using state‐of‐the‐art multiscale computational techniques, emerging properties in monolayer CdO are predicted. The data show an optical transition dominated by direct excitations and characterized by a direct‐bandgap of 3.16 eV. The intrinsic spontaneous polarization and ferroelectricity with a rather high electromechanical coupling coefficient observed in monolayer CdO make it a candidate material for applications in optoelectromechanical nanodevices.